Are Both I-Deals? the Mediating Role of I-Task and I-Incentive in the Relationship Between Supervisor Support and Employees’ Silence and Voice - Lopez-Bohle, S; Muñoz-Medina, L (SAGE Publications Inc., 2024)
Informed by Social Exchange Theory, this study has developed a mediation model that explains the role of I-deals in the relationship between perceived supervisor support and employees’ discretionary behaviors (i.e., voice and silence). Using a sample of 140 Chile employees, results from our structural equation modeling, indicated that the relationship between supervisor support and employees’ voice (positive) and silence (negative) was mediated by task I-deals. However, we found that the relationship between supervisor support and employees’ voice (negative) was mediated by task I-incentive while this type of I-deals did not mediate the relationship between supervisor support and employees’ silence. This research expands the I-deals literature by focusing on the provision of I-deals to their subordinates and by analyzing the outcomes of incentive I-deals and task I-deals to employees’ discretionary behaviors. Supervisors and HR departments might utilize task I-deals to help facilitate desirable employee outcomes, namely more voice and less silence. © The Author(s) 2024.